A case of central diabetes insipidus associated with cardiac dysfunction. Issue 12 (11th October 2016) - Ohara, Nobumasa; Kaneko, Masanori; Suwabe, Tatsuya; Yoshie, Tasuku; Kuwano, Hiroyuki; Ebe, Katsuya; Fujita, Toshio; Fuse, Koichi; Kaneko, Kenzo; Kamoi, Kyuzi
Key Clinical Message: Central diabetes insipidus (CDI) results from a deficiency of arginine vasopressin (AVP) secretion. It is treated by replacement therapy with the synthetic AVP analogue desmopressin. To prevent heart failure in patients with CDI accompanied by cardiac dysfunction, controlling sodium and water intake is essential, using the minimum effective dose of desmopressin. Abstract : Central diabetes insipidus (CDI) results from a deficiency of arginine vasopressin (AVP) secretion. It is treated by replacement therapy with the synthetic AVP analogue desmopressin. To prevent heart failure in patients with CDI accompanied by cardiac dysfunction, controlling sodium and water intake is essential, using the minimum effective dose of desmopressin.